2021
DOI: 10.1108/ihr-09-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Pivot! How the restaurant industry adapted during COVID-19 restrictions

Abstract: PurposeThe purpose of this systematic review is to highlight some of the business model changes restaurants, bars and beverage producers undertook to modify their operations in order to not only stay in business but also to better serve their employees and communities during the COVID-19 crisis.Design/methodology/approachAn analysis was conducted on 200 industry articles and categorized into three major themes: expansion of take-out/delivery, innovative practices, and community outreach/corporate support, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 2 publications
1
46
0
6
Order By: Relevance
“…The COVID-19 pandemic has affected not only health but also economic and social issues, including difficulties in trade in goods and services (Minondo 2021), restaurant activities (Norris et al 2021), travel restrictions (Gupta et al 2021;Arshad et al 2021), and education (Yıldırım et al 2021). The coronavirus pandemic has left its mark on nearly all organizations that were forced to immediately respond.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The COVID-19 pandemic has affected not only health but also economic and social issues, including difficulties in trade in goods and services (Minondo 2021), restaurant activities (Norris et al 2021), travel restrictions (Gupta et al 2021;Arshad et al 2021), and education (Yıldırım et al 2021). The coronavirus pandemic has left its mark on nearly all organizations that were forced to immediately respond.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Perusahaan harus berusaha menawarkan layanan dan produk yang menguntungkan menggunakan metode pengiriman yang inovatif sebagai dasar diferensiasi baru, sehingga memberikan nilai yang lebih besar bagi pelanggan (Chen et al dalam Saad, 2020). Layanan ini mendukung upaya menjaga jarak sosial dan membatasi titik kontak penyebaran COVID-19, sehingga banyak restoran meluncurkan platform pemesanan online untuk situs web mereka dan memperluas kemitraan pengiriman pihak ketiga mereka (Noris, Taylor Jr dan Taylor, 2021).…”
Section: Pendahuluanunclassified
“…One of the areas particularly affected by the adverse effects of the pandemic was the economy and businesses representing various industries. The main concerns were directed toward the issue of maintaining the supply chain continuity in economic systems (Aday&Aday, 2020;Chowdhury et al, 2021), and among the industries particularly affected by the pandemic, such as the hotel and tourism industry (D'Orazio et al, 2021;Davahli et al, 2020), the food service industry (Harms et al, 2021;Norris et al, 2021), or the fitness industry (Komańda, 2020;Park & Kwon, 2022) were indicated. However, all the industries that were related to the movement of people and/or their meetings among people can be pointed out as those that encountered exceptional difficulties, especially during lockdowns.…”
Section: Introductionmentioning
confidence: 99%